Kebijakan Perlindungan Sosial Indonesia pada Situasi Krisis Corona Virus Disease 2019 - Heri Nugroho; Zulfa Ruhama (Kementerian Koordinator Bidang Pembangunan Manusia dan Kebudayaan Republik Indonesia, 2021)
This study aims to analyze changes in social protection policies in Indonesia during the COVID-19 pandemic crisis. The Covid-19 pandemic has had an impact on the economic crisis, which has occurred in both developed and developing countries. The policy of limiting human mobility is something that needs to be done to reduce greater losses. This makes the use of technology increasingly intense to maintain the role of the welfare state and a better social protection system in Indonesia. This study aims to understand the changes in the social protection system implemented in response to the Covid-19 pandemic. The method used is exploratory qualitative approach. This study yielded three important findings. First, Indonesia has had various social protection programs built since the 1998 crisis and continued to be developed until the Covid-19 pandemic. Second, Indonesia has carried out the role of the welfare state by implementing and controlling a combination of social protection strategies that include a combination of expanding social assistance, developing social assistance programs, adding social assistance programs, and restructuring social assistance programs in response to the Covid-19 crisis. Third, the specific characteristics of the Covid-19 pandemic have changed Indonesia's social protection system to become more numerous and varied, widening the budget deficit to accommodate an increase in the social assistance budget and national economic recovery, as well as the use of technology for updating databases and distributing social protection more accurately.